ANNUAL FINANCIAL STATEMENTS OF GERMAN CORPORATIONS. - Kosiol, Erich (The Accounting Review, 1938)
Abstract In line with the suggestions of the Committee on Corporation Law of the Academy of German Law, the new act of January 30, 1937, relating to stocks has retained the anonymity which depends upon subsuming under one head many separate kinds of capital, and to make up for the resulting personification has significantly strengthened the position of the administrative officers, so that the leadership notion which stands for authority and responsibility takes the place of the nonsensical majority principle. The direction of the company lies exclusively in the hands of the Management, which controls it in an orderly and conscientious manner, bearing full responsibility for the welfare of the enterprise and its employees and contributing to the common good of both the people and the Reich. The stockholders who up to now possessed the last word even on questions of business policy, at present exercise this power only on authorization by the management. Whatever the opinions otherwise of stockholders on this matter, their importance is purely advisory and the management is not legally required to abide by them. The official text of the corporation law explicitly limits the scope of stockholders' power to questions involving the economic and legal structure of the company.